The Knowledge Level of Housewives about Serving Ayam Betutu - Yoga Pratama, Agus Darma; Mirsa Umiyati; Daimond Tavares Rosa Suhartono (RETORIKA: Jurnal Ilmu Bahasa, 2021)
This study analyzed the knowledge level of housewives about serving Ayam Betutu/Chicken Betutu as a Balinese specialty. The population in this study was 103 housewives who lived in Banjar Buaji Anyar, Sumerta Kelod Village. The data were collected using direct interviews and standardized questionnaires. The data processing was performed using the SPSS program, while a descriptive statistic was used to analyze the data. Based on the results of data analysis, the study showed that the knowledge level of housewives about serving Chicken Betutu was still very good. Definitely, this is a very good thing for the preservation of Chicken Betutu as special food, and especially Chicken Betutu has become a culinary icon from Bali. The good knowledge level of housewives about serving Chicken Betutu can be a trusted source for the younger generation if they want to know about Chicken Betutu, starting from the basic ingredients, the manufacturing process, tools, to the taste of the Chicken Betutu.